Blood biochemical values in Japanese Black calves in Kagoshima Prefecture, Japan - OTOMARU, Konosuke (J Vet Med Sci, 2015)
To obtain blood biochemical basic data of Japanese Black calves in Kagoshima Prefecture, Japan, blood samples were obtained from 582 clinically healthy calves on 27 farms. Calves were divided into three stages: the suckling stage (between 14 and 90 days of age, n=191), the early growing stage (between 91 and 180 days of age, n=200) and the late growing stage (between 181 and 270 days of age, n=191). The mean concentration of total cholesterol, triglyceride, nonesterified fatty acids, calcium and zinc, and the mean activities of γ-glutamyltransferase and alkaine phospatase in the suckling stage were significantly higher than those in the early and late growing stages (P<0.01). The mean concentration of total protein, albumin and globulin increased gradually with growing. The mean concentration of beta-hydroxybutyrate in the suckling stage was below 150 µmol/l, however, it elevated above 400 µmol/l in the early and late growing stages. The mean concentration of copper concentration was above 70 µg/dl in all stages. The mean concentration of zinc was between 90 and 110 µg/dl in all stages. These results suggest that the blood biochemical values of Japanese Black calves vary with growing stages, and the blood parameters obtained in this study are considered useful as indices for health management of Japanese Black calves.